In vivo fitness of carbapenem-resistant Acinetobacter baumannii strains in murine infection is associated with treatment failure in human infections. (January 2022) - Nutman, Amir; Temkin, Elizabeth; Lellouche, Jonathan; Rakovitsky, Nadya; Hameir, Amichay; Daikos, George; Durante-Mangoni, Emanuele; Pavleas, Ioannis; Dishon, Yael; Petersiel, Neta; Yahav, Dafna; Eliakim, Noa; et al.
Abstract: Objectives: Mortality among patients with carbapenem-resistant Acinetobacter baumannii (CRAB) infections varies between studies. We examined whether in vivo fitness of CRAB strains is associated with clinical outcomes in patients with CRAB infections. Methods: Isolates were collected from patients enrolled in the AIDA trial with hospital-acquired pneumonia, bloodstream infections and/or urinary tract infections caused by CRAB. The primary outcome was 14-day clinical failure, defined as failure to meet all criteria: alive; haemodynamically stable; improved or stable Sequential Organ Failure Assessment (SOFA) score; improved or stable oxygenation; and microbiological cure of bacteraemia. The secondary outcome was 14-day mortality. We tested in vivo growth using a neutropenic murine thigh infection model. Fitness was defined based on the CFU count 24 hours after injection of an inoculum of 10 5  CFU. We used mixed-effects logistic regression to test the association between fitness and the two outcomes. Results: The sample included 266 patients; 215 (80.8%) experienced clinical failure. CRAB fitness ranged from 5.23 to 10.08 log CFU/g. The odds of clinical failure increased by 62% for every 1-log CFU/g increase in fitness (OR 1.62, 95% CI 1.04–2.52). After adjusting for age, Charlson score, SOFA score and acquisition in the intensive care unit, fitness remained significant (adjusted OR 1.63, 95% CI 1.03–2.59). CRAB fitness had a similar effect on 14-day mortailty, although the association was not statistically significant (OR 1.56, 95% CI 0.95–2.57). It became significant after adjusting for age, Charlson score, SOFA score and recent surgery (adjusted OR 1.88, 95% CI 1.09–3.25). Conclusions: In vivo CRAB fitness was associated with clinical failure in patients with CRAB infection.